Attractiveness of High School students for the teaching career: A case study in the South of Minas Gerais (Research, Society and Development, 2022)
Brazil is experiencing a serious crisis in the teaching profession arising from a shortage of professionals in the labor market. Some of the main factors contributing to this growing crisis are low salaries and also the devaluation of the profession. In this sense, this study had as main objective to investigate the attractiveness of students graduating from high school for the teaching career in the municipality of Machado, South of Minas Gerais. For this, 150 questionnaires were applied to students from public and private schools present in the municipality. Data analysis showed that there is a low interest among the students interviewed in following the teaching career, however, there is a portion that still shows interest in the career. Students consider that the teacher, most of the time, is an example to be followed. This aspect makes the teacher the main vehicle of communication between the profession and the student. In this way, it is essential that it makes a good reference to your career.